A study on brand awareness in hospital industry - SHAKILA.P (International Journal of Pharma and Bio Sciences, 2017)
This paper examines on brand awareness helps in creation of demand of hospital services. It states how brand awareness is created using trust, customer satisfaction, brand loyalty, hospital image and relationship commitment. Branding is an important strategy for differentiating a product from its competitors. It is different in services elements of brand awareness are differing from the tangible goods. It is a name, logo, trademark, patent number or package design that is used to distinguish the firm product or services from others. Through the brand awareness is identify a firm services in the hospital or recall its brand whenever he thinks about services. Brand awareness has to be thought of as “a continuous range from an uncertain feeling that a brand is recognized to a belief that it is only one in the product class”. This study investigates role of brand awareness of hospital services is budding by different strategies.A study was undertaken to analyze the Brand awareness of Manipal Hospital inSalem District. Manipal Hospital in Salem District strength is that their quality of services and branding techniques. The research is conducted to analyze the brand awareness of the respondents, to know the effectiveness of advertisement towards the competitors. The main objective of the study is to analyze the Brand awareness of the respondents. Descriptive research is used for the study and convenience sampling technique is adopted. The data required for the study is collected through questionnaire and for further information secondary data is gathered from the reports of the industry and websites. The data collected is analyzed by simple percentage, weighted average, Correlations. Based on the analysis and interpretation the findings and suggestions are provided to the organization for further improvementThrough the brand awareness is identify a firm services in the hospital or recall its brand whenever he thinks about services. Brand awareness has to be thought of as a continuous range from an uncertain feeling that a brand is recognized to a belief that it is only one in the product class.